(untitled) (Innovation & Development in Engineering and Applied Science, 2025)
In Ecuador there are fair trade organizations that provide support to small producers who continually work empirically; FEPP CAMARI is a social organization that promotes equitable, fair and supportive marketing in society. Therefore, this study shows a methodological proposal of the strategic plan focused on small producers with fundamental and friendly strategic axes for efficient and effective execution.